What affects drivers' satisfaction with autonomous vehicles in different road scenarios?. (November 2021) - Li, Mengfan; Feng, Zhongxiang; Zhang, Weihua; Zhu, Shunying
Highlights: This is one of the first study to study drivers' satisfaction on autonomous vehicle. Self-efficacy and mental workload are considered as main affecting factors. The influence of different road scenarios (simple, medium and complex) are studied. The effect of mental workload on satisfaction is mediated by driving self-efficacy. Abstract: With the increasing popularity of autonomous vehicles, it is important to understand their user satisfaction because such aspects are likely to determine their future development. This article studied the effects of perceived benefit, perceived risk, interpersonal feelings, infrastructure adaptability, driving self-efficacy and mental workload on satisfaction when using autonomous vehicles, designed three road scenarios (simple, general, and complex), and established a structural equation model of satisfaction with mediators. A total of 553 responses were retrieved through online questionnaires, the path coefficients among various factors and indicators were calculated, and the importance of each factor in different road scenarios was discussed. The results show that the six factors have different association with user satisfaction in different road scenarios. The effect of mental workload on satisfaction in all road scenarios is mediated by self-efficacy. These results provide insights for the improvement of the autonomous vehicle industry.